2020
DOI: 10.2147/ott.s263980
|View full text |Cite
|
Sign up to set email alerts
|

<p>Serum CXCL13 Level is Associated with Tumor Progression and Unfavorable Prognosis in Penile Cancer</p>

Abstract: Background: Chemokine (C-X-C motif) ligands (CXCLs) are important regulators of tumor progression in many cancers and could serve as potential cancer biomarkers. However, the expression patterns as well as functions of CXCLs remain unclear in penile cancer (PC). The aim of this study was to evaluate the usefulness of serum CXCL13 as a potential cancer biomarker for PC. Patients and Methods: This retrospective study enrolled 76 patients diagnosed with PC between 2016 and 2018. Serum CXCL13 level was detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Different types of immune cells could be recruited into the tumor microenvironment via interactions between chemokines and chemokine receptors (Nagarsheth et al, 2017). Altered expression levels of chemokines in malignant tumors are associated with angiogenesis, proliferation, metastasis and recruitment and activation of immune cells in multiple tumors (Strieter et al, 2005;Teicher and Fricker, 2010;Santoni et al, 2014;Li et al, 2017;Yang et al, 2017;Liang et al, 2018;Mo et al, 2020;Yang et al, 2020). Many anti-chemokine drugs have been used in combination with other antitumor drugs in cancer treatment (Feig et al, 2013;Salazar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Different types of immune cells could be recruited into the tumor microenvironment via interactions between chemokines and chemokine receptors (Nagarsheth et al, 2017). Altered expression levels of chemokines in malignant tumors are associated with angiogenesis, proliferation, metastasis and recruitment and activation of immune cells in multiple tumors (Strieter et al, 2005;Teicher and Fricker, 2010;Santoni et al, 2014;Li et al, 2017;Yang et al, 2017;Liang et al, 2018;Mo et al, 2020;Yang et al, 2020). Many anti-chemokine drugs have been used in combination with other antitumor drugs in cancer treatment (Feig et al, 2013;Salazar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that RAB20 and IDO1 overexpression promote cell proliferation and induce immunosuppression in PSCC [12,21]. Other serum biomarkers, such as CXCL5, CXCL13 and CCL20, are associated with nodal metastasis in small cohorts [33][34][35]. The mechanisms underlying tumor metastasis are uncertain and have become an imminent issue.…”
Section: Discussionmentioning
confidence: 99%
“…High preoperative serum levels of mentioned chemokines were associated with tumor progression and poor outcomes. That is why scientists suggest using CCL20, CXCL13 and CXCL5 as diagnostic and prognostic biomarkers [133][134][135].…”
Section: Role Of Stat3 In Penile Cancermentioning
confidence: 99%